2019
DOI: 10.1093/jnci/djz045
|View full text |Cite
|
Sign up to set email alerts
|

Combined Tumor Sequencing and Case-Control Analyses of RAD51C in Breast Cancer

Abstract: Background Loss-of-function variants in RAD51C are associated with familial ovarian cancer, but its role in hereditary breast cancer remains unclear. The aim of this study was to couple breast tumor sequencing with case-control data to clarify the contribution of RAD51C to hereditary breast cancer. Methods RAD51C was sequenced in 3080 breast cancer index cases that were negative in BRCA1/2 clinical tests and 4840 population-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 38 publications
3
31
0
Order By: Relevance
“…They found that 16.9% of included patients carried BRCA1/2 mutations and 6.8% of patients had non-BRCA1/2 mutations including TP53, PALB2, CHEK2, ATM, BARD1, BRIP, CDH1 and RAD50. Recent studies reported that mutations in PALB2 and RAD51C were found to be an important cause of HBOC [24,25]. Additionally, CDH1 mutations were not found in the Western study but detected in the Chinese study.…”
Section: Discussionmentioning
confidence: 81%
“…They found that 16.9% of included patients carried BRCA1/2 mutations and 6.8% of patients had non-BRCA1/2 mutations including TP53, PALB2, CHEK2, ATM, BARD1, BRIP, CDH1 and RAD50. Recent studies reported that mutations in PALB2 and RAD51C were found to be an important cause of HBOC [24,25]. Additionally, CDH1 mutations were not found in the Western study but detected in the Chinese study.…”
Section: Discussionmentioning
confidence: 81%
“…In contrast to mutations in BRCA1 and BRCA2, which predispose individuals to both BC and OC, BRIP1, RAD51C, and RAD51D are predominantly OC risk genes, while their role in BC is less defined and questionable [20,21,27,74,75,[93][94][95][96]. Despite certain relationships between mutations in the discussed genes and OC, more precise risk estimation is required.…”
Section: Discussionmentioning
confidence: 99%
“…While BRCA1 is the most recognized predisposing gene for BC and OC, RAD51C was first identified as a putative cancer-predisposing gene in BC/OC families in 2010 [15]. Subsequently, it was confirmed to be associated with an increased risk of OC and, only recently, of BC, in particular of the TN type [16,17]. Moreover, to date somatic epimutations in both BC [5,10,18,19] and OC [10,19,20] have been identified only at these two genes.…”
Section: Discussionmentioning
confidence: 99%